2019
DOI: 10.3390/su11226232
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior Mechanism of the Urban Joint Distribution Alliance under Government Supervision from the Perspective of Sustainable Development

Abstract: Urban joint distribution is closely related to the national economy and people’s livelihood, and governments and enterprises play an active role in the process of urban joint distribution. From the perspective of government regulations, this paper explores the mechanism and evolution law of the behavior of an urban joint distribution alliance. Based on the evolutionary game theory, a model of homogeneous enterprises participating in urban joint distribution operations under the guidance of government regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition, government is an important external stakeholder for an enterprise, whose regulatory approach will greatly affect the implementation of responsible innovation [22].Faced with ethical safety issues in innovation activities, governments of various countries have promulgated a series of policies and measures to promote responsible innovation. These policy measures include the European Union's "Horizon 2020" 8th R & D framework plan [23], the American "National Nano Plan Environmental, Health and Safety Strategic Research Plan" [24] and the Chinese "13th five-year plan for scientific and technological innovation" [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, government is an important external stakeholder for an enterprise, whose regulatory approach will greatly affect the implementation of responsible innovation [22].Faced with ethical safety issues in innovation activities, governments of various countries have promulgated a series of policies and measures to promote responsible innovation. These policy measures include the European Union's "Horizon 2020" 8th R & D framework plan [23], the American "National Nano Plan Environmental, Health and Safety Strategic Research Plan" [24] and the Chinese "13th five-year plan for scientific and technological innovation" [25].…”
Section: Introductionmentioning
confidence: 99%
“…Through the above analysis, the supervision departments can adopt the narrow precision supervision mode, broad precision mode, or a combination of both. Based on this, this paper gives some policy implications to relevant government departments [31,32]:…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Zhao et al [23] showed that government supervision provides a better environment for market incentives and that market behavior must be regulated by the synergistic effect of government regulation and market incentives. Zhang et al [24] developed a model of homogeneous enterprises participating in urban joint distribution operations under the guidance of government regulations and explored the mechanism and evolution law of the behavior of an urban joint distribution alliance. Zhang et al [25] constructed an evolutionary game model to analyse the quality of government supervision in the dynamic interaction between a government and vaccine manufacturers under different supervision modes.…”
Section: Government Mechanismsmentioning
confidence: 99%